Meneropong collective entrepreneurship dan manajemen strategis pada Toko/Warung Madura - Hidayat, Ujang Syaiful; Hariyanto, Dwi Widi; Susanto, Iwan Wahyu (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2023)
Abstract: Many Madurese-owned stalls or retail shops with similar facades, items, prices, and opening 24/365 in major cities across Indonesia have gone viral on social media, making them an intriguing retail chain phenomenon to investigate. At a glance, this phenomenon opposes conventional strategic management, which emphasizes competitive advantage. This qualitative study uses observation, interviews, and document analysis to gain insight into the strategic management paradigm was held in Surabaya and Madura. The results show that these retail stores are sporadic in nature, not retail chains. No coherent management strategy has been planned, applied, or assessed. The Madurese genius loci that becomes their philosophy of living, when put into practice, gives rise to a novel approach to corporate strategy. Keywords: Strategic management, collective entrepreneurship, retails, Madura.